EFFECTS OF NUTRIENTS AND BODY MEASUREMENTS ON MORTALITY RISK IN FRAIL PEOPLE. (11th November 2018) - Jayanama, K; Theou, O; Blodgett, J; Cahill, L; Rockwood, K
Abstract: Emerging evidence suggests that appropriate nutritional care can mitigate frailty and its complications. We investigated the association between nutrition and frailty across the life course, including the effect of nutrition-related parameters on mortality in frail people. Participants aged ≥20 years with frailty and nutrition data (n=8, 482) from the 2003–2006 cohorts of the National Health and Nutrition Examination Survey were included. Four anthropometric parameters and 33 nutrients with established cut points obtained by 24-hour dietary recall were studied. A frailty index (FI) was constructed from 36 items, excluding items related to nutrition; 1, 160 people (13.7%) were classified as frail (FI>0.25). Mortality data were obtained from death certificate records until 2011. We performed Cox regression analysis adjusting for age, sex, and energy intake. The percentage of individuals with abnormal nutritional parameters significantly increased with higher frailty for 22 nutrients (e.g. energy, protein, tocopherol, folate, cobalamin, essential fatty acid, omega-3 intake) and all anthropometric measures. In frail people, low body mass index (HR 4.56, 95%CI 2.29–9.06), tocopherol (2.40, 1.07–5.40), skin fold (1.65, 1.20–2.26), and energy consumption (1.59, 1.21–2.09) and weight loss (1.44, 1.09–1.91) were significantly associated with higher mortality risk. Low fat intake (0.61, 0.37–0.99) and being overweight (0.73, 0.57–0.95) were associated with lower mortality risk. Most nutritional parameters changed with frailty but not all increased the mortality risk in frail people. Being underweight and having low tocopherol intake was highly associated with increased mortality risk whereas being overweight and having low fat intake was associated with decreased mortality risk in frail people.